The Response of Different Shading Applications in Terms of Yield, Quality and Antioxidant in Tomato Plant - Kartal, Adnan; Akhoundnejad, Yelderem; Dasgan, Hayriye Yildiz; Temur, Baki; Ersoy, Lale (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2024)
In the study, the effects of different 40%, 55%, 75% and 95%) shading levels on yield and quality of tomato (Kamenta F 1 ) plant were investigated. The experiment was carried out in the growing season of 2020 (April -August). In the experiment, leaf temperature, chlorophyll content, leaf relative water content, macro and micro nutrient concentration in green parts, water-soluble dry matter and pH content in tomato juice, total phenolic and flavonoid content in green parts, fruit yield and number of fruits were examined in the experiment. As a result of the study, there was an increase in leaf temperature in plants under control (without sading) application. Shading applications were effective in the relative water content of the leaves, the amount of chlorophyll and the increase in fruit yield. It has been observed that 55% shading application is more effective in fruit yield than other applications. As a result, it was concluded that the shading applications applied positively affected the fruit yield and quality of Kamenta F 1 tomato variety.
Keywords: Antioxidant; Tomato; Shading; Phenolic; Flavonoid